Best Practice Policy: The Effectiveness of Natural Gas Line Program in Lontong Neighborhood Surabaya - Fierda Nurany (SOSHUM : Jurnal Sosial dan Humaniora, 2023)
The goal of this study is to describe how the natural gas line program was put into place in micro, small, and medium enterprises (MSMEs) in the Lontong neighbourhood of Surabaya, where craftsmen use LPG a lot.Â  The theory used to make sense of the phenomenon is called policy effectiveness, and it consists of the following components: 1) availability; 2) breadth; 3) depth; 4) bias; 5) responsibility; and 6) appropriateness. In addition, both qualitative and descriptive types of research were used. Ten lontong artisans, three PGN members, and two subdistrict officials are among the informants. Since 2016, residents of the lontong neighbourhood have been using natural gas lines in their factories, according to the results. Socialization of the retail space spreads the word to locals about the program. Information about the program is readily available to each subdistrict thanks to a sales area representative and a call centre open around the clock. Monthly program usage can range from 200m3 to 1,500m3, and the program is available to both single-family homes and small and medium-sized businesses. However, many people are still unaware of the benefits of using natural gas, so the natural gas line program needs to be socialized.